EFFECTS OF ISLAMIC MEDICINE AND ITS MANAGEMENT: AN OVERVIEW OF MUSLIM SCHOLARS IN BIDA EMIRATE OF NIGER STATE, NIGERIA - Abdulrahman Yahaya; Umar Saidu Alhaji (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2022)
The focus of this paper is Islamic medicine and its management: an overview of Muslim scholars in Bida Emirate of Niger State, Nigeria. This paper would identify the sources of Islamic medicine from its origin which some scholars relied upon for the treatment of people. It reveals Muslim healers and types of medicinal applications and some herbal concoctions that Muslim scholars use for the treatment of ailments of people in the emirate. Islamic medicine occupation has been an age long tradition since the advent of Islam which is another popular means of solving some ailments of Muslims. The paper adopts explanatory method for sourcing data in respect of this subject as these method is so encompassed that would bring out the efficacy of Islamic healing on people. It is therefore, believed that the will of Islamic medicine determines people’s actions and or inactions due to it divine nature from Allah. The paper would proffer some suggestions to the people on efficient and effective management of Islamic medicines on the treatment of ailment challenges among people in accordance with the tenets of Islam.